(untitled) (Journal of the College of Basic Education, 2019)
The intention of this paper is to find the exact and split sequences of the sub modules of FW6-second and third pair of hooks representation modules, when F be a field of characteristic 0 . This intention is revealing by presenting the main results theorems (3-1) and (3-2), where we gave two of this kind of sequences. 0 0 Here we refer that depending on the structural constructing of the elements (modules) of these sequences or it‘s sub modules by counting the dimensions was essential for proving these theorems.